1986
DOI: 10.1016/0014-5793(86)81376-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of HLA genes using pulsed‐field gradient electrophoresis

Abstract: The technique of pulsed-field gradient electrophoresis (PFGE) allows the determination of gene linkage relationships since DNA fragments up to 2 Mb can be separated. PFGE was employed to study linkage of class I, II and III genes belonging to the human major histocompatibility (HLA) complex. The results establish that the class II DOD and DZa genes are linked with the DP subregion, centromeric to the DQ/DX-DR-C4 chromosomal segment, and allow us to estimate the minimal length of the entire HLA complex. Pulsed-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
14
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…This technique has been used to determine the arrangement of the class II genes within a region of 900 kb (14) and to provide a version of the whole MHC (15) slightly different from that presented here and not including the TNF genes. In addition, the class II and class III regions were linked within a common 1000-kb Not I restriction fragment (15,16). These studies suggested, on the basis of a linear alignment of restriction fragments hybridizing with class II, class III, or class I coding sequence probes, that the entire MHC spans about 2000-3000 kb.…”
mentioning
confidence: 91%
“…This technique has been used to determine the arrangement of the class II genes within a region of 900 kb (14) and to provide a version of the whole MHC (15) slightly different from that presented here and not including the TNF genes. In addition, the class II and class III regions were linked within a common 1000-kb Not I restriction fragment (15,16). These studies suggested, on the basis of a linear alignment of restriction fragments hybridizing with class II, class III, or class I coding sequence probes, that the entire MHC spans about 2000-3000 kb.…”
mentioning
confidence: 91%
“…Using PFGE, Hardy et al (10) determined a map for the human class II region and established the order of the HLA-D subregions. Physical linkage between the human class II and class III loci has also been demonstrated using this technique (11,12). In mouse the orientation and molecular map position of the complement gene cluster have been established (13).…”
mentioning
confidence: 99%
“…The technique of pulsed-field gel electrophoresis (PFGE) (8,9), which allows the resolution of DNA fragments >2 megabases, in combination with restriction enzymes that cut rarely in the mammalian genome, has been used for long-range restriction-site mapping of the MHC in man (10)(11)(12) and in mouse (13). Using PFGE, Hardy et al (10) determined a map for the human class II region and established the order of the HLA-D subregions.…”
mentioning
confidence: 99%
“…The physical length of the entire HLA complex is unknown so far, but our estimate based on the separation of DNA fragments containing HLA genes by pulsed-field gel electrophoresis (Schwartz andCantor 1984, Carle andOlson 1984) indicates that it encompasses at least 2500 kb pairs (Ragoussis et al 1986). This estimate has recently been confirmed (Lawrance et al 1987).…”
mentioning
confidence: 96%
“…Mutant BM 19.7 is a monosomy 6 mutant cell line retaining the A2 haplotype (Ziegler et al 1985b). BM 28.7 also exhibits monosomy 6, but with loss of the chromosome bearing the A2 haplotype (Ragoussis et al 1986). In the interstitial deletion mutant BM 2.2.3, the class I region of the A2 haplotype has been deleted, but the class II and III regions of this haplotype are still present, as is the chromosome 6 carrying the A1 haplotype (Ziegler et al 1985a).…”
mentioning
confidence: 99%